The Problem of the Authenticity The Endless Debate Between Revisionist and Traditionalist New Perspectives - Ulum, Muhammad Babul (Proceedings of International Conference on Muslim Society and Thought, 2024)
The authenticity of hadith is an endless debate between the western and Islamic worlds, mainly due to different points of view. The nonconformity arose because the study of the Islamic world focused on dogmatic ideological nuances, while western world studies adopted a more critical and academic methodology. The present study aimed to explore how these two opposing viewpoints assessed the hadith of the Prophet. The studies conducted by Goldziher and Schacht were selected as representatives of the Western world and those of Azami for Islam. Azami, a leading traditionalist Islamic scholar, had tried to counter both from an academic perspective. Furthermore, other Islamic scholars often reiterate the opinion of Azami when rejecting theses of Goldziher and Schacht. This study attempted to answer three main questions using the abductive method, namely, How do the Western and Islamic perspectives view the hadith of the Prophet? What argument was put forward by Azami for refuting the views of Goldziher? Why does Goldziher opinion continue to get stronger despite the numerous attacks